Dropped-out Students and the Decision to Drop-out in Hungary - Pusztai, Gabriella; Fényes, Hajnalka; Szigeti, Fruzsina; Pallay, Katalin (Central European Journal of Educational Research, 2019)
The interpretation of the phenomenon of student dropout, which represents a waste of a relatively large proportion of human and material capital in the social, individual and institutional domain, is impossible without examining dropout students. In this study, we analysed the DEPART 2018 database, which contains data from 605 Hungarian dropout students. We tried to identify higher education dropout scenarios and pointed out that higher educational dropout is a complex phenomenon. Based on the students’ reports on their interpretation and evaluation of their dropouts, four student clusters were created. We compared the groups with their socio-cultural background and their decision to drop out from higher education, and their assessment of that decision. The most important result of the study is that it identifies a new group in addition to the international dropout types, and provides a detailed picture that calls our attention to the diversity of dropout groups, thereby moving beyond the over-generalised image of the dropout student.